2006
DOI: 10.1021/bi051915z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Efavirenz Binding on the Subunit Equilibria of HIV-1 Reverse Transcriptase

Abstract: Recent studies showed that nonnucleoside reverse transcriptase inhibitors (NNRTIs) have variable effects on dimerization of p66 and p51 subunits of HIV-1 reverse transcriptase (RT). Efavirenz, one of three NNRTIs currently used in highly active anti-retroviral therapy, enhances subunit dimerization. Sedimentation equilibrium experiments on each subunit and equimolar mixtures of both subunits were used to measure dissociation constants for the three coupled dimerization reactions of RT in the absence and presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(119 citation statements)
references
References 39 publications
(79 reference statements)
7
107
5
Order By: Relevance
“…S4C, S4D, and S4E, respectively. the p51 homodimer (K d ϭ 230 M) (25). For each of the RT bait-prey combinations strong signals were obtained, whereas background signals were consistently low (supplemental Fig.…”
Section: In Situ Monitoring Of Ppis and Their Modulation In Response mentioning
confidence: 96%
“…S4C, S4D, and S4E, respectively. the p51 homodimer (K d ϭ 230 M) (25). For each of the RT bait-prey combinations strong signals were obtained, whereas background signals were consistently low (supplemental Fig.…”
Section: In Situ Monitoring Of Ppis and Their Modulation In Response mentioning
confidence: 96%
“…It has been demonstrated that some NNRTIs act as chemical enhancers of HIV-1 RT heterodimerization (Tachedjian et al, 2001;Venezia et al, 2006). To date, efavirenz was found to be the most potent enhancer of RT heterodimerization, whereas nevirapine has a weak effect and delavirdine has no effect at all (Tachedjian et al, 2001).…”
Section: Nnrtis Act As Potent Inhibitors Of Hiv-1 Rt Dimerizationmentioning
confidence: 99%
“…First, RT truncation mutations involving the Trp repeat motif significantly impair PR-mediated Gag processing (30). Second, efavirenz (EFV)-a nonnucleoside reverse transcriptase inhibitor (NNRTI) that greatly enhances HIV-1 RT dimerization in vitro (46,47)-is capable of suppressing virion production by enhancing the efficiency of PR-mediated Gag and Gag-Pol cleavage (14,45). However, a W401A alanine substitution mu-tation that abrogates RT dimerization in vitro (49) almost completely negates the EFV inhibitory effect on virion production (9).…”
Section: Gag-polmentioning
confidence: 99%